Lithium ion battery positive electrode layered oxide with prism-surface shared layered structure and preparation method and application of lithium ion battery positive electrode layered oxide

By using ion exchange additives to assist liquid-phase ion exchange in the preparation process of lithium-ion battery positive electrode materials, the problem of complex reaction control and insufficient ion exchange in the prior art is solved, and a high-purity prism-shared layered structural material is obtained, which significantly improves its structural stability and electrochemical properties.

CN119503897AActive Publication Date: 2025-02-25XI AN JIAOTONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411706096.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode material preparation methods are complex in the reaction control, and the micromorphic structure is not easy to control, resulting in the impact of structural stability and electrochemical properties, and it is difficult to achieve full exchange during ion exchange, resulting in low purity of shared structures in the prism.

Method used

Ion exchange additives are used to assist liquid phase Li+/AM+ (AM = Na+ or K+) ion exchange, and layered oxide precursors containing alkaline earth metal are synthesized by high-temperature calcination, and nano-layered oxides are added as additives during the liquid phase ion exchange process to promote the uniformity and adequacy of ion exchange.

Benefits of technology

It effectively improves the ion exchange rate and obtains a high-purity surface-sharing layered structure lithium-ion battery positive electrode material, improves the structural stability and electrochemical performance of the material, and has excellent cycling performance. It is suitable for the preparation of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503897A_ABST
    Figure CN119503897A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery positive electrode layered oxide with an edge-surface shared layered structure and a preparation method and application thereof, and belongs to the technical field of lithium ion battery positive electrode materials. The preparation method comprises the following steps: synthesizing a layered oxide precursor containing sodium or potassium through high-temperature calcination, immersing the layered oxide precursor containing sodium or potassium into a solution containing lithium salt, and adding a nano layered oxide ion exchange auxiliary agent for liquid-phase ion exchange. In the ion exchange process, the nano layered oxide is adsorbed on the surface of the precursor, so that the reaction activation energy is reduced, and the uniformity and consistency of the exchange process are improved. And filtering, washing and drying to finally obtain the prismatic surface shared layered structure. The method comprises the steps of high-temperature calcination and ion exchange, and specifically provides raw materials and operation conditions. The prepared material has a laminated structure shared by prism surfaces of the lithium oxide octahedron and the cobalt oxide octahedron, is uniform in particles, controllable in particle size, high in material capacity and excellent in cycle performance, and can be widely applied to the electronic product and power automobile market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a lithium ion battery positive electrode layered oxide with a facet-sharing layered structure, and a preparation method and application thereof. Background Art

[0002] In recent years, high energy density lithium-ion batteries have played a vital role in promoting electric vehicles, electronic devices, large-scale energy storage and many other fields. The development of lithium-ion batteries with higher energy density has always been a goal that people continue to pursue. Among the main components of lithium-ion batteries, the positive electrode material has become a key factor restricting the improvement of energy density. Therefore, the development of positive electrode materials plays a vital role in the success of lithium-ion batteries.

[0003] Layered oxide cathode materials, such as lithium cobalt oxide (LiCoO2) and lithium nickel cobalt manganese oxide Li(Ni,Co,Mn)O2 materials, have attracted widespread attention in the field of lithium-ion batteries in recent years due to their high discharge voltage and large discharge capacity. Specifically, as a traditional cathode material, layered oxide cathode materials have a high theoretical capacity and a high voltage platform, which gives them a significant advantage in improving battery energy density. For cobalt-free lithium-manganese-rich layered oxide cathode materials, their advantages lie not only in their high discharge capacity, but also in their relatively abundant raw material resources and relatively low cost, which makes them have great potential in low-cost, long-life battery applications.

[0004] However, in the crystal structure of the current mainstream layered oxide positive electrode materials, the lithium oxygen (LiO6) octahedron and the transition metal oxygen (TMO6) octahedron are arranged in a co-edge arrangement. During electrochemical cycles, this crystal structure is prone to interlayer slip, which not only causes significant changes in the crystal structure, but also produces lattice defects, further increasing the mechanical stress of the material. This structural change will block the diffusion channel of lithium ions, affect the efficiency of lithium ion insertion and deinsertion, and thus cause poor battery cycle stability and a sharp drop in capacity. Layered oxide materials with facet-sharing structures have a large vacancy steric hindrance to the migration of transition metal ions after the lithium ions are released, because one side of the LiO6 octahedron is coplanar with the TMO6 octahedron, so the facet-sharing structural characteristics effectively hinder the migration of metal ions, showing excellent structural stability and electrochemical performance. However, there are many difficulties in the current synthesis process of this material. Due to its metastable structural characteristics, the difficulty of synthesis is significantly increased, the requirements for raw materials are extremely harsh, the control of the synthesis reaction is extremely complex, and the regulation of its microstructure is also challenging. Although the currently widely used ion exchange method can obtain facet-sharing structures, it is difficult to achieve sufficient ion exchange during the exchange process, and the purity of the obtained facet structure is not high. It is urgent to further optimize the synthesis method to obtain high-purity facet-sharing structures. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a facet-sharing layered structure lithium ion battery positive electrode layered oxide and its preparation method and application, so as to solve the technical problems that the existing preparation method has complex reaction control, the microscopic morphology structure is not easy to control, resulting in the stability of the layered oxide structure and electrochemical performance being affected, and it is difficult to achieve sufficient ion exchange during the exchange process, and the purity of the obtained facet-sharing structure is not high. The method of the present invention can effectively improve the ion exchange rate and obtain a high-purity facet-sharing layered structure lithium ion battery positive electrode layered oxide material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a facet-sharing layered structure and a preparation method thereof. The invention lies in that an ion exchange auxiliary agent is used to assist the liquid phase Li + / AM + (AM = Na + or K + ) Ion exchange, methods include: First, alkaline earth metal-containing layered oxide AM was synthesized by high-temperature calcination. m [Li x Ni y Co z Mn 1-x-y-z ]O2 (where AM = Na + or K + ). The synthesized layered oxide is immersed in a solution containing a lithium salt, and a liquid phase ion exchange treatment is carried out, and an ion exchange aid is added during the treatment process. Finally, the product is filtered, washed and dried to prepare a facet-sharing layered structure; Among them, 0.50≤ m ≤1.00,0.00≤ x ≤0.33; 0.00≤ y ≤1.00; 0.00≤ z ≤1.00.

[0007] The present invention discloses a method for preparing a facet-sharing layered structure, comprising the following steps: 1) High temperature calcination According to the chemical formula AM m [Li x Ni y Co z Mn 1-x-y-z]O2, weigh the sodium source (or potassium source), lithium source, nickel source, cobalt source and manganese source respectively, and mix them thoroughly. Then, pre-sinter the mixture at 500-600℃ for 3-8h, and then calcine at 700-1000℃ for 5-20h. After calcination, cool the mixture naturally to room temperature, thereby obtaining a sodium or potassium layered oxide precursor AM. m [Li x Ni y Co z Mn 1-x-y-z ]O2. AM represents Na or K, 0.50≤ m ≤1.00,0.00≤ x ≤0.33,0.00≤ y ≤1.00,0.00≤ z ≤1.00; 2) Ion exchange The precursor oxide AM prepared in step 1) m [Li x Ni y Co z Mn 1-x-y-z ]O2 is mixed with a lithium salt solution with a concentration in the range of 0.5-5 mol / L, and a liquid phase ion exchange treatment is carried out at a reaction temperature of 120-280°C with the assistance of an ion exchange aid for a treatment time of 0.5-8 hours. Afterwards, it is centrifuged, washed and dried, and the collected product is a lithium-ion battery positive electrode layered oxide Li with an edge-sharing layered structure. m [Li x Ni y Co z Mn 1-x-y-z ]O2.

[0008] Preferably, in step 1), it is characterized in that, in step 1), the sodium source is sodium carbonate (Na2CO3) or sodium hydroxide (NaOH); the potassium source is sodium carbonate (K2CO3) or sodium hydroxide (KOH); the lithium source is lithium carbonate (Li2CO3) or lithium hydroxide monohydrate (LiOH·H2O) or lithium nitrate (LiNO3) or lithium acetate (LiCH3COO); the nickel source is nickel oxide (NiO), nickel oxalate (NiC2O4) or nickel carbonate (NiCO3); the cobalt source is cobalt oxalate (CoC2O4), cobalt tetroxide (Co3O4), cobalt trioxide (Co2O3) or cobalt carbonate (CoCO3); the manganese source is manganese oxalate (MnC2O4), manganese monoxide (MnO), manganese dioxide (MnO2) or manganese carbonate (MnCO3).

[0009] Preferably, in step 1), the sintering is heated at a heating rate of 0.2-5° C. / min.

[0010] Preferably, in step 2), the lithium salt is lithium nitrate (LiNO3), lithium chloride (LiCl), lithium hydroxide monohydrate (LiOH·H2O) or lithium acetate (LiCH3COO).

[0011] Preferably, in step 2), the solvent of the lithium salt solution is deionized water.

[0012] Preferably, in step 2), the ion exchange aid is a lithium-embedded nano-layered oxide (Li x CoO2、Li x MnO2、Li x NiO2、Li x TiO2、Li x VO2 or Li x AlO2), where 0.3≤ x ≤0.8.

[0013] Further preferably, in step 2), the amount of the ion exchange aid used is 0.1-10% by mass relative to the precursor.

[0014] Further preferably, the precursor oxide AM m [Li x Ni y Co z Mn 1-x-y-z ]The dosage ratio of O2 to lithium salt solution is 1mg:(5-200)μL.

[0015] The invention also discloses a material with a facet-sharing layered structure prepared by the method.

[0016] The arrangement of interlayer polyhedrons in the crystal structure of the layered material has been effectively regulated, with a face-sharing structure of lithium oxygen octahedrons and cobalt oxygen octahedrons.

[0017] Preferably, the added ion exchange additive is a lithium-embedded nano-layered oxide (Li x CoO2、Li x MnO2、Li x NiO2、Li x TiO2、Li x VO2 or Li x AlO2, where 0.30≤ x ≤0.80), and its addition amount is 0.1%-10% of the mass of the layered oxide material of the potassium ion battery. With its assistance, ion exchange treatment is carried out to obtain a layered lithium battery positive electrode material with an edge face sharing structure.

[0018] Preferably, the added ion exchange additive is a lithium-embedded nano-layered oxide (Li x CoO2、Li x MnO2、Li x NiO2、Li x TiO2、Li x VO2 or Li x AlO2, where 0.30≤ x ≤0.80), and its addition amount is 0.1%-10% of the mass of the layered oxide material of the sodium ion battery. With its assistance, ion exchange treatment is carried out to obtain a layered lithium battery positive electrode material with an edge-sharing structure.

[0019] Preferably, the layered lithium battery positive electrode material with facet-sharing structure is composed of micron-sized particles, the grain size of which is within the range of 1-20 microns, and the particle size is controllable.

[0020] The invention also discloses the application of the above-mentioned layered lithium battery positive electrode material with facet sharing structure in the preparation of lithium ion batteries.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a positive electrode layered oxide of a lithium ion battery with a facet-sharing layered structure. The core invention lies in that during the preparation process, an ion exchange auxiliary agent is used to assist the liquid phase Li + / AM + (AM =Na + or K + ) for ion exchange. On the one hand, directly through the high-temperature solid phase method and the liquid phase ion exchange method, an environment with highly controllable temperature, time and ion concentration is provided, the ion diffusion effect is good, the exchange process is fast, uniform and sufficient, the equipment is cheap and universal, the process is simple and mature, and it has the advantages of energy saving, emission reduction, cost reduction and efficiency improvement; on the other hand, the ion exchange process is assisted by the nano-layered oxide ion exchange additive. The nano-layered oxide is adsorbed on the surface of the precursor, and its role is similar to that of a catalyst, which adsorbs the sodium in the bulk phase of the precursor to the surface, and allows the lithium in the lithium salt solvent to enter the interior of the precursor structure. Reduce the reaction activation energy, enhance the ion transfer efficiency, ensure the uniformity and consistency of the exchange process, and promote the full ion exchange. The layered positive electrode material prepared by this method has excellent electrochemical properties, uniform particle distribution, controllable particle size, good batch uniformity, and the method is simple in process, easy to operate, and the material structure is stable and reliable.

[0022] The facet-sharing layered structure lithium-ion battery positive electrode layered oxide prepared by the method of the present invention has excellent cycle performance. Under the conditions of 3.0-4.6V and 1C, the capacity retention rate of the material is still as high as more than 84% after 100 cycles. Therefore, it can be used to prepare lithium-ion batteries, and then can be widely used in the electronic products and power vehicle markets. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The schematic diagram of the auxiliary mechanism of the ion exchange process using the nano-layered oxide ion exchange auxiliary agent of the present invention; Figure 2 A schematic diagram of the crystal structure of the facet-sharing layered structure prepared by the present invention; Figure 3 The X-ray diffraction spectrum of the lithium cobalt oxide positive electrode material with facet-sharing layered structure prepared in Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the lithium cobalt oxide positive electrode material with a facet-sharing layered structure prepared in Example 1 of the present invention; Figure 5 The charge-discharge curve of the lithium cobalt oxide positive electrode material with facet-sharing layered structure prepared in Example 1 of the present invention at 0.1C; Figure 6 The cycle performance of the lithium cobalt oxide positive electrode material with facet-sharing layered structure prepared in Example 1 of the present invention at a 1C rate; Figure 7 The X-ray diffraction spectrum of the lithium cobalt oxide positive electrode material with a partially faceted shared layered structure prepared in Comparative Example 1 of the present invention; Figure 8 The X-ray diffraction spectrum of the lithium cobalt oxide positive electrode material with facet-sharing layered structure prepared in Example 2 of the present invention; Fig. 9 This is a scanning electron microscope image of the lithium cobalt oxide positive electrode material with a facet-sharing layered structure prepared in Example 2 of the present invention; Fig.10 The charge-discharge curve of the lithium cobalt oxide positive electrode material with facet-sharing layered structure prepared in Example 2 of the present invention at 1C; Fig.11 The X-ray diffraction spectrum of the lithium-rich manganese-based positive electrode material with a partially faceted shared layered structure prepared in Example 3 of the present invention; Fig.12 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material with a facet-sharing layered structure prepared in Example 3 of the present invention; Fig.13 The charge and discharge curves of the lithium-rich manganese-based positive electrode material with a facet-sharing layered structure prepared in Example 3 of the present invention at 0.1C. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Figure 1 The method for preparing the facet-sharing layered structure disclosed in the present invention uses liquid phase Li + / AM + (AM = Na + or K + ) Ion exchange method. First, the sodium or potassium layered oxide precursor AM is directly prepared by high-temperature solid-phase sintering and calcination. m [Li x Ni y Co z Mn 1-x-y-z ]O2, and then put it in a solution together with a lithium salt solution, add an ion exchange aid, mix it thoroughly, and then carry out a liquid phase ion exchange treatment. After filtering, washing, and drying, the facet-shared layered oxide Li m [Li x Ni y Co z Mn 1-x-y-z ]O2.

[0027] The facet-shared layered oxide Li prepared by the present invention m [Li x Ni y Co z Mn 1-x-y-z]The crystal structure diagram of O2 is as follows Figure 2 The oxide material has a layered structure in which the edges of lithium oxygen octahedron and cobalt oxygen octahedron share a common surface, and the particles are uniform and the particle size is controllable.

[0028] Example 1 The precursor used in this embodiment is a potassium ion battery layered oxide KCoO2, and the prepared positive electrode material is LiCoO2. Specifically, the method for preparing a facet-sharing layered structure lithium ion battery LiCoO2 positive electrode material comprises the following steps: Step 1. High temperature calcination: According to the chemical formula KCoO2, the molar ratio of potassium and cobalt elements is 1.0:1.0, and the corresponding KCO3 and Co2O3 are weighed respectively. The two are placed in a ball mill and mixed thoroughly, and then the mixture is placed in a muffle furnace. Under air atmosphere conditions, the furnace temperature is raised to 500°C at a heating rate of 5°C / min, and pre-burned at this temperature for 6 hours. Subsequently, the temperature is continued to be raised at a heating rate of 5°C / min until the temperature reaches 850°C, and then calcined at this temperature for 18 hours. After the calcination is completed, the material is allowed to cool naturally to room temperature, thereby obtaining a precursor material, namely, a potassium ion layered oxide precursor KCoO2 with triangular prisms and octahedrons sharing edges; Step 2. Ion exchange: The potassium ion layered oxide precursor KCoO2 obtained in step 1 is immersed in a 1 mol / L LiOH·H2O aqueous solution, wherein the ratio of potassium ion layered oxide precursor to LiOH·H2O solution is 1:5 mg / μL, and then added to the reactor. At the same time, 1% of the mass percentage of ion exchange additive Li 0.7 MnO2 was subjected to liquid phase ion exchange treatment at a reaction temperature of 150°C for 2 hours. After the treatment, it was centrifuged and washed with ethanol three times, and the resulting product was collected after drying. This product is the positive electrode layered oxide LiCoO2 of lithium-ion batteries with a facet-sharing layered structure.

[0029] The XRD pattern of LiCoO2 prepared in this example is shown in Figure 3 From the XRD diagram, we can see that all the diffraction peaks belong to the facet-sharing layered structure, and the space group is P6 3 mc , belonging to the hexagonal system. The SEM image of the lithium ion layered oxide with facet-sharing layered structure prepared in this embodiment is shown in Figure 4 The particle size is about 5 μm.

[0030] The charging and discharging performance test process of the positive electrode material prepared in this embodiment is as follows: The positive electrode material prepared in this embodiment is used as the active material, acetylene black is the conductive agent, and polyvinylidene fluoride is the binder. The active material, the conductive agent, and the binder are uniformly mixed in a ratio of 8:1:1. Then, 30 times the mass of the binder is added dropwise with nitrogen methyl pyrrolidone, and stirred to make it into a slurry. The slurry is evenly applied to the aluminum foil, then placed in a constant temperature drying oven at 120 ° C and dried for 12 hours. After drying to constant weight, a small disc with a diameter of 12 mm is punched out using a punching machine, which is the positive working electrode. While ensuring that there is no water, the small disc is placed in a glove box filled with argon. A lithium sheet is used as the counter electrode and reference electrode, a polypropylene film Celgard 2400 is used as a diaphragm, and the electrolyte uses 1M LiPF6 / EC+DEC (volume ratio of 1:1), and finally assembled into a button battery of model CR2023 in the glove box.

[0031] Charge and discharge performance test: The facet-sharing layered structure positive electrode material LiCoO2 prepared in this embodiment was tested at 25°C, a voltage range of 3.0-4.65V, and 0.1C. The first charge and discharge capacities were 257.5mAh / g and 253.9mAh / g, respectively. Figure 5 The capacity retention rate after 100 cycles of electrochemical cycling at a voltage range of 3.0-4.6V and 1C is 84%, as shown in Figure 2. Figure 6 shown.

[0032] Example 2 The precursor used in this embodiment is a potassium ion battery layered oxide KCoO2, and the prepared positive electrode material is LiCoO2. Specifically, the method for preparing a lithium ion battery LiCoO2 positive electrode material with a partially faceted shared layered structure includes the following steps: Step 1. High temperature calcination: According to the chemical formula KCoO2, the molar ratio of potassium and cobalt elements is 1.0:1.0, and the corresponding KCO3 and Co2O3 are weighed respectively. The two are placed in a ball mill and mixed thoroughly, and then the mixture is placed in a muffle furnace. Under air atmosphere conditions, the furnace temperature is raised to 500°C at a heating rate of 3°C / min, and pre-burned at this temperature for 6 hours. Subsequently, the temperature is continued to be raised at a heating rate of 1°C / min until the temperature reaches 850°C, and then calcined at this temperature for 18 hours. After the calcination is completed, the material is allowed to cool naturally to room temperature, thereby obtaining a precursor material, that is, a potassium ion layered oxide precursor KCoO2 with triangular prisms and octahedrons sharing edges; Step 2. Ion exchange: The potassium ion layered oxide precursor KCoO2 obtained in step 1 is immersed in a 1 mol / L LiOH·H2O aqueous solution, wherein the ratio of potassium ion layered oxide precursor to LiOH·H2O solution is 1:5 mg / μL, and then added to the reactor. At the same time, an ion exchange additive Li 0.3 VO2, and subjected to liquid phase ion exchange treatment at a reaction temperature of 250°C for 2 hours. After the treatment, it was centrifuged and washed with deionized water for 3 times, and the obtained product was collected after drying. This product is the positive electrode layered oxide LiCoO2 of lithium-ion battery with facet-sharing layered structure.

[0033] The XRD pattern of LiCoO2 with a partially faceted shared layer structure prepared in this example is shown in Figure 2. Figure 7 From the XRD diagram, we can see that some diffraction peaks belong to the facet-shared layered structure, which belongs to P6 3 mc Space group.

[0034] Example 3 The precursor used in this embodiment is sodium ion layered oxide NaCoO2, and the prepared positive electrode material is LiCoO2. Specifically, the method for preparing the facet-sharing layered structure lithium-ion battery LiCoO2 positive electrode material includes the following steps: Step 1. High temperature calcination: According to the chemical formula NaCoO2, the molar ratio of sodium and cobalt elements is 1.0:1.0, and the corresponding Na2CO3 and Co2O3 are weighed respectively. The two are placed in a ball mill and mixed thoroughly, and then the mixture is placed in a muffle furnace. Under air atmosphere conditions, the furnace temperature is raised to 500°C at a heating rate of 5°C / min, and pre-burned at this temperature for 6 hours. Subsequently, the temperature is continued to be raised at a heating rate of 3°C / min until the temperature reaches 850°C, and then calcined at this temperature for 18 hours. After the calcination is completed, the material is allowed to cool naturally to room temperature, thereby obtaining a precursor material, namely, a potassium ion layered oxide precursor NaCoO2 with triangular prisms and octahedrons sharing edges; Step 2. Ion exchange: The sodium ion layered oxide precursor NaCoO2 obtained in step 1 is immersed in a 1 mol / L LiOH·H2O aqueous solution, wherein the ratio of the sodium ion layered oxide precursor to the LiOH·H2O solution is 1:5 mg / μL, and then added to the reactor. At the same time, an ion exchange additive Li 0.5CoO2 was treated with liquid phase ion exchange at a reaction temperature of 120°C for 8 hours. After the treatment, it was centrifuged and washed with ethanol three times. The resulting product was collected after drying. This product is the positive electrode layered oxide LiCoO2 of lithium-ion batteries with a facet-sharing layered structure. The XRD pattern of LiCoO2 prepared in this example is shown in Figure 8 From the XRD diagram, we can see that all the diffraction peaks belong to the facet-sharing layered structure, and the space group is P6 3 mc , belonging to the hexagonal system. The SEM image of the lithium ion layered oxide with facet-sharing layered structure prepared in this embodiment is shown in Fig. 9 , the particle size is about 5μm.

[0035] Charge and discharge performance test: The test method is the same as that of Example 1. The results show that the first charge and discharge capacities of the LiCoO2 positive electrode material with facet-sharing layered structure prepared in this example are 254.7 mAh / g and 249.3 mAh / g respectively at a test temperature of 45°C, a voltage range of 3.0-4.6 V, and 1C. Fig.10 .

[0036] Example 4 The precursor used in this example is the sodium ion battery layered oxide Na[Li 0.15 Ni 0.25 Mn 0.6 ]O2, the positive electrode material prepared in this embodiment is Li[Li 0.15 Ni 0.25 Mn 0.6 Specifically, the method for preparing a positive electrode material for a lithium-ion battery with a facet-sharing layered structure comprises the following steps: Step 1. High temperature calcination: According to the chemical formula Na[Li 0.15 Ni 0.25 Mn 0.6 ]O2 ingredients, the molar ratio of sodium, lithium, nickel and manganese elements is 1.0:0.15:0.25:0.60, and the corresponding Na2CO3, Li2CO3, NiO and MnO are weighed respectively. Place them in a ball mill and mix them thoroughly, then put the mixed materials into a muffle furnace. Under air atmosphere conditions, the furnace temperature is raised to 500°C at a heating rate of 5°C / min, and pre-burned at this temperature for 6h. Subsequently, the temperature is continued to be raised at a heating rate of 0.2°C / min until the temperature reaches 1000°C, and then calcined at this temperature for 18h. After calcination, the material is allowed to cool naturally to room temperature, thereby obtaining a precursor material, that is, a sodium ion layered oxide Na[Li 0.15 Ni 0.25 Mn 0.6]O2; Step 2. Ion exchange: The sodium ion layered oxide precursor Na[Li 0.15 Ni 0.25 Mn 0.6 ]O2 was immersed in a 2mol / L LiOH·H2O aqueous solution, in which the ratio of sodium ion layered oxide precursor to LiOH·H2O solution was 1:25mg / μL, and then added to the reactor. At the same time, a mass percentage of Na[Li 0.15 Ni 0.25 Mn 0.6 ]O2 is 2% of the ion exchange auxiliary agent LiMnO2, and the liquid phase ion exchange treatment is carried out at a reaction temperature of 280°C for 8 hours. After the treatment, centrifugal separation is carried out, and the product is washed with deionized water three times, and then dried and collected. This product is the positive electrode layered oxide Li[Li 0.15 Ni 0.25 Mn 0.6 ]O2.

[0037] The Li[Li 0.15 Ni 0.25 Mn 0.6 ]XRD of O2 Fig.11 From the XRD diagram, we can see that all the diffraction peaks belong to the facet-sharing layered structure, and the space group is P6 3 mc , belonging to the hexagonal system. The SEM image of the lithium ion layered oxide with facet-sharing layered structure prepared in this embodiment is shown in Fig.12 , the particle size is about 2-5μm.

[0038] The electrochemical performance test of the battery was carried out at 25°C, in the voltage range of 2.0-4.8V, and 0.1C. The results showed that the positive electrode material Li[Li 0.15 Ni 0.25 Mn 0.6 ]O2 has the first charge and discharge capacities of 256.8 mAh / g and 205.4 mAh / g at a rate of 0.1C. Fig.13 shown.

[0039] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a layered oxide for a positive electrode of a lithium-ion battery with a facet-sharing layered structure, characterized in that: include: The metal salt raw materials are uniformly mixed and synthesized into a sodium or potassium-containing layered oxide precursor by high-temperature calcination; the sodium or potassium-containing layered oxide precursor is immersed in a solution containing a lithium salt, and a lithium-embedded nano-layered oxide is added as an ion exchange aid to perform a liquid phase ion exchange treatment; The treated reaction system is filtered, washed and dried to obtain a positive electrode layered oxide for lithium-ion batteries with a facet-sharing layered structure.

2. The method for preparing the positive electrode layered oxide of lithium-ion battery with facet-sharing layered structure according to claim 1, characterized in that: The following steps are involved: 1) According to the chemical formula AM m [Li x Ni y Co z Mn 1-x-y-z ]O2 ratio, weigh the metal salt raw materials sodium source or potassium source, lithium source, nickel source, cobalt source and manganese source respectively, mix them evenly, then pre-sinter them at 500-600℃, then calcine them at 700-1000℃, and after cooling, obtain a layered oxide precursor, which is expressed as AM m [Li x Ni y Co z Mn 1-x-y-z ]O2; AM represents Na or K, 0.50≤ m ≤1.00,0.00≤ x ≤0.33,0.00≤ y ≤1.00,0.00≤ z ≤1.00; 2) The prepared layered oxide precursor and lithium salt solution are mixed, and then lithium-embedded nano-layered oxide is added as an ion exchange aid at 120-280°C to assist in ion exchange treatment, and then the reaction system is centrifuged, washed and dried to obtain a facet-sharing layered structure lithium-ion battery positive electrode layered oxide, whose composition expression is Li m [Li x Ni y Co z Mn 1-x-y-z ]O2.

3. The method for preparing the positive electrode layered oxide of lithium ion battery with facet-sharing layered structure according to claim 2, characterized in that: In step 1), the pre-sintering treatment time is 3-8 hours, the high-temperature calcining treatment time is 5-20 hours, and the high-temperature sintering is carried out at a heating rate of 0.2-5°C / min starting from the pre-sintering temperature.

4. The method for preparing the positive electrode layered oxide of lithium-ion battery with facet-sharing layered structure according to claim 2, characterized in that: In step 1), the sodium source is sodium carbonate or sodium hydroxide; the potassium source is potassium carbonate or potassium hydroxide; the lithium source is lithium carbonate, lithium hydroxide monohydrate, lithium nitrate or lithium acetate; the nickel source is nickel oxide, nickel oxalate or nickel carbonate; the cobalt source is cobalt oxalate, cobalt tetroxide, cobalt trioxide or cobalt carbonate; the manganese source is manganese oxalate, manganous oxide, manganese dioxide or manganese carbonate.

5. The method for preparing the positive electrode layered oxide of lithium-ion battery with facet-sharing layered structure according to claim 2, characterized in that: In step 2), the lithium salt solution is prepared from lithium nitrate, lithium chloride, lithium hydroxide monohydrate or lithium acetate, and the concentration is 0.5-5 mol / L; the dosage ratio of the layered oxide precursor and the lithium salt solution is 1 mg: (5-200) μL.

6. The method for preparing the positive electrode layered oxide of lithium-ion battery with facet-sharing layered structure according to claim 2, characterized in that: In step 2), the ion exchange aid is a lithium-intercalated nano-layered oxide, including Li x CoO2、Li x MnO2、Li x NiO2、Li x TiO2、Li x VO2 or Li x AlO2, where 0.3 ≤ x ≤0.

8.

7. The method for preparing the positive electrode layered oxide of lithium-ion battery with facet-sharing layered structure according to claim 2, characterized in that: In step 2), the amount of the ion exchange aid is 0.1%-10% of the mass of the layered oxide precursor.

8. A layered oxide for positive electrode of lithium ion battery with facet-sharing layered structure prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The facet-sharing layered structure lithium-ion battery positive electrode layered oxide is composed of micron-sized particles, the grain size is distributed in the range of 1-20 microns, and the particle size is controllable.

9. The facet-sharing layered structure lithium-ion battery positive electrode layered oxide according to claim 8, characterized in that: The facet-sharing layered structure lithium-ion battery positive electrode layered oxide has a thermodynamically metastable layered structure and belongs to P6 3 mc Space group.

10. Use of the facet-sharing layered structure lithium ion battery positive electrode layered oxide according to claim 8 or 9 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Single-crystal lithium ion battery positive electrode material with different layered structures as well as preparation method and application of single-crystal lithium ion battery positive electrode material

    CN114956210A

  • Metastable-phase lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

    CN116443940A

  • O3, O2 and T2 type lithium battery positive electrode material as well as ultrasonic-assisted liquid-phase ion exchange preparation method and application thereof

    CN118954627A

  • Nonaqueous electrolyte secondary battery and method of forming positive electrode

    US20100173202A1